Strategic Optimization With Decision Theory: Unpacking the Operations Research Framework for Effective Decision Making - Munthe, Putri Enjelita; Harahap, Lokot Muda; Hadiwijaya, Rangga; Ginting, Dionisius; Suwarno, Iin; Syahputra, Reza; Ananda, Tanya (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
Making the right decisions can optimize resource utilization, increase operational efficiency, and strengthen competitive positions in the market. A decision, as a choice of action from various alternatives that fulfill one or more goals, has a significant impact on various related parties. Therefore, decision making is the main function for a leader, both in companies and public institutions. The technique of modifying data to increase its value and usefulness is known as data optimization. This entails converting unstructured data into a structured format, improving data quality, reducing duplication, and retrieving related information. This research was conducted using a narrative review model. The research method used is secondary data collected from various international journals, papers, and previous research papers used as data sources and analyzed by the author taking into account the problems considered in this research.